1994
DOI: 10.1364/ol.19.001122
|View full text |Cite
|
Sign up to set email alerts
|

Four-photon-mixing-mediated stimulated Raman scattering in a multimode optical fiber

Abstract: Stimulated Raman scattering with 532-nm pulsed laser light is investigated in a 7.9-microm-core step-index multimode fiber. While low-intensity pump or single-mode LP(01) excitation produces the usual stimulated Raman scattering light, mixed-mode (LP(01) + LP(02)) excitation with pump intensities of ~5 kW uniformly shifts the multiorder Stokes Raman spectrum by an amount determined by fiber parameters, thus making stimulated Raman scattering tunable. This is due to the mediating influence of the four-photon mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…We observed that the shift is reversed if the input pump beam is aligned back with the center of the fiber core. Similar observations of the effect of the FWM processes on shifting the SRS spectrum have been reported by Sharma et al 17 ; they have shown that the cascaded Raman peaks can shift depending on which modes are excited by the pump laser.…”
supporting
confidence: 85%
“…We observed that the shift is reversed if the input pump beam is aligned back with the center of the fiber core. Similar observations of the effect of the FWM processes on shifting the SRS spectrum have been reported by Sharma et al 17 ; they have shown that the cascaded Raman peaks can shift depending on which modes are excited by the pump laser.…”
supporting
confidence: 85%
“…The output spectra from single G-or P-doped bre ( gure 2) exhibit the combined e ects of SRS and FWM. For a Gdoped bre, the rst peak at 539 nm in the output spectrum corresponds to the FWM line, which agrees with other observations in a pure silica bre [11]. The cascade peaks show the FWM-mediated SRS which is o set from the normal SRS by 240 cm 1 .…”
Section: Experimental Set-up and Resultssupporting
confidence: 89%
“…The combination of SRS and FWM in G-doped bre is mutually bene cial. Raman-assisted FWM [13] leads to the earlier occurrence of the FWM and FWM-mediated SRS [11] produces the cascade SRS with a lower threshold.…”
Section: Theoretical Model and Numerical Simulationsmentioning
confidence: 99%
“…Here, the GA provides an optimized collection of modes on the SLM that generates a selective FWM interaction to pull the average wavelength down. Similar spectral-shifts can be achieved by manually adjusting the input coupling of the fiber 38,54 . However, the SLM provides a systematic and controlled feedback methodology that allows precise modal excitation for the desired results.…”
Section: Figure 3: Wavefront Shaping Of Srs Peaks (A) 3rd Srs Peak Omentioning
confidence: 96%
“…The SLM provides continuous control over the spectrum to produce the desired output by controlling the mixture of modes at the input of the MMF. The spectral shifts of the cascade are obtained by mixed-mode excitation 38,54 . Here, the GA provides an optimized collection of modes on the SLM that generates a selective FWM interaction to pull the average wavelength down.…”
Section: (C) 5th Srs Peak Optimization the Green Square Marks The Spe...mentioning
confidence: 99%